Já não sei se era mito essa história de lobo mau: o sistema de proteção social brasileiro para crianças e adolescentes vítimas de violência - Souza, Julia Ketlin Santos de (My University, 2025)
This Final Course Project (TCC) in Social Work discusses the social protection system for children and adolescents. The research question is: How does the Brazilian social protection system act for children and adolescents who are victims of violence? The objective is to analyze the performance of the Brazilian social protection system for children and adolescents who are victims of violence. In this construction, the analysis was carried out using Marx's Critical Dialectical Method, as well as its categories: Historicity, Totality, Contradiction, and Mediation. As a methodological procedure, bibliographic and documentary research were used. Initially, this work presents a historical overview of the process of building Brazilian social protection for children and adolescents, with information from 1919 until the promulgation of the Statute of the Child and Adolescent in 1988. After conducting a data analysis based on the research "Violence against children and adolescents (2019-2021)" carried out by the Brazilian Forum of Public Security and the José Luiz Egydio Setúbal Foundation in November 2021, which provided information on five types of crimes against children and adolescents—bodily injury, mistreatment, rape, sexual exploitation, and intentional violent death—this study reflects on the professional work of social workers in assisting children and adolescents who are victims of violence. It examines the types of social protection and services available to these individuals. Finally, it addresses the interdisciplinary work among professionals within the Unified Social Assistance System (SUS). In conclusion, it is evident that despite the continued prevalence of violence against children and adolescents in our society, the importance of the social worker's role in social protection services, working alongside an interdisciplinary team, is evident. [resumo fornecido pelo autor]
O presente Trabalho de Conclusão de Curso (TCC) em Serviço Social discorre sobre o sistema de proteção social para crianças e adolescentes. A problematização desta pesquisa é: Como se dá a atuação do sistema de proteção social brasileiro para as crianças e adolescentes vítimas de violência? Com o objetivo de analisar a atuação do sistema de proteção social brasileiro às crianças e adolescentes vítimas de violência. Nesta construção, a análise se dá a partir do Método Dialético Crítico de Marx, bem como suas categorias: Historicidade, Totalidade, Contradição, Mediação. Já como procedimento metodológico, utilizou-se a pesquisa bibliográfica e a pesquisa documental. No presente trabalho, inicialmente, construiu-se um resgate histórico do processo de construção da proteção social brasileira às crianças e adolescentes, com informações desde 1919 até a promulgação do Estatuto da Criança e do Adolescente em 1988. Após realizou-se uma análise de dados a partir da pesquisa Violência contra crianças e adolescentes (2019-2021) realizada pelo Fórum Brasileiro de Segurança Pública e a Fundação José Luiz Egydio Setúbal, de novembro de 2021, que dispunha de informações de cinco tipos crimes contra crianças e adolescentes, os quais são: lesão corporal, maus-tratos, estupro, exploração sexual e morte violenta intencional. A partir disto, reflete-se sobre o trabalho profissional do assistente social frente ao atendimento de crianças e adolescentes vítimas de violência, onde se compreendeu os os tipos de proteção social e os serviços voltados a estes sujeitos. Por fim, abordou-se sobre o trabalho interdisciplinar entre os trabalhadores do Sistema Único de Assistência Social. Ao final percebeu-se que apesar da violência contra criança e adolescente ainda se manifestar em nossa sociedade nota-se a importância do trabalho do profissional assistente social na atuação nos serviços da rede proteção social em conjunto com a equipe interdisciplinar. [resumo fornecido pelo autor]
Keywords: Serviço social; Crianças - Maus-tratos; Violência contra adolescentes; Política Pública; Assistentes sociais